1987
DOI: 10.1073/pnas.84.21.7677
|View full text |Cite
|
Sign up to set email alerts
|

Brain-type prostaglandin D synthetase occurs in the rat cochlea.

Abstract: Prostaglandin D synthetase [(5Z,13E

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0
1

Year Published

1991
1991
2007
2007

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 24 publications
1
18
0
1
Order By: Relevance
“…Inner ear hair cells play an essential role in the auditory pathway that converts sound stimulation into electrical signals and then into a neural code. In the adult rat cochleas, the L-PGDS immunoreactivity was found in inner and outer hair cells, their supporting cells (Claudius' cells and Deiters' cells), marginal cells, basal cells, and cells of Reissner's membrane (Tachibana et al 1987). However, it remains to be investigated whether L-PGDS is expressed in intermediate cells.…”
Section: Sound Melanocytes Are Required For Sound Sensingmentioning
confidence: 99%
“…Inner ear hair cells play an essential role in the auditory pathway that converts sound stimulation into electrical signals and then into a neural code. In the adult rat cochleas, the L-PGDS immunoreactivity was found in inner and outer hair cells, their supporting cells (Claudius' cells and Deiters' cells), marginal cells, basal cells, and cells of Reissner's membrane (Tachibana et al 1987). However, it remains to be investigated whether L-PGDS is expressed in intermediate cells.…”
Section: Sound Melanocytes Are Required For Sound Sensingmentioning
confidence: 99%
“…This enzyme is responsible for biosynthesis of PGD2 in the brain, while several other enzymes, such as GSH-requiring PGD synthase and GSH S-transferase, also catalyze the reaction to produce PGD2 and are present in various other rat tissues (4). The enzyme is localized in the central nervous system (4) and associated tissues, such as the retina (5) and cochlea (6). Furthermore, postnatal changes in the cellular localization of this enzyme have been observed in the brain (7) and cochlea (6).…”
mentioning
confidence: 99%
“…The enzyme is localized in the central nervous system (4) and associated tissues, such as the retina (5) and cochlea (6). Furthermore, postnatal changes in the cellular localization of this enzyme have been observed in the brain (7) and cochlea (6). For example, the enzyme is distributed in most neurons in the brain of 1-to 2-week-old rats, but the major localization site shifts to oligodendrocytes in adult animals (7).…”
mentioning
confidence: 99%
“…1). Among several enzymes catalyzing the conversion of PGH2 to PGD2, glutathioneindependent PGD synthase [prostaglandin-H2 D-isomerase; (5Z,13E)-(15S)-9a,lla-epidioxy-15-hydroxyprosta-5,13-dienoate D-isomerase, EC 5.3.99.2] (2) is responsible for biosynthesis of PGD2 in the central nervous system (3), retina (4), and cochlea (5). Immunocytochemical studies with a polyclonal and two monoclonal anti-rat brain PGD synthase antibodies revealed that the major cellular location of the enzyme in the brain shifts postnatally from neurons of 1-to 2-week-old rats to oligodendrocytes in adult animals (6), suggesting that the enzyme may have distinct functions in those cells at each specific developmental stage and thus plays important roles in both maturation and maintenance of the central nervous system.…”
mentioning
confidence: 99%